Joint associations of objectively-measured sedentary behavior and physical activity with health-related quality of life - Loprinzi, Paul D. (Prev Med Rep, 2015)
No studies, to my knowledge, have examined the joint effects of physical activity and sedentary behavior on health-related quality of life (HRQOL), which was the purpose of this study. Data from the 2003–2006 National Health and Nutrition Examination Survey (NHANES) were used (N = 5,536). Moderate-to-vigorous physical activity (MVPA) and sedentary behavior were assessed using an ActiGraph 7164 accelerometer, with HRQOL assessed using the Centers for Disease Control and Prevention 4-item HRQOL index. MVPA (β(adjusted) = − 0.01; 95% CI: − 0.01 to − 0.004; P < 0.001), but not sedentary behavior (β(adjusted) = − 0.0003; 95% CI: − 0.001–0.0001; P = 0.37), was associated with HRQOL. MVPA was associated with HRQOL among those above the median (≥ 487.5 min/day) level of sedentary behavior (β(adjusted) = − 0.02; 95% CI: − 0.03 to − 0.01; P = 0.006; N = 2769). The results of this brief report do not demonstrate that sedentary behavior, independent of MVPA, is associated with HRQOL. The independent association of MVPA on HRQOL confirms previous work that used self-report measures of MVPA.